A holistic approach to school-based counselling and guidance services in Malaysia - Low, Sew Kim; Kok, Jin Kuan; Lee, Mah Ngee (School psychology international, 2013)
Counselling services in Malaysian schools were first established in 1963. Several local research studies investigated the provision of school counselling services and revealed that they were unpopular among students and could be further improved. School-aged children are still under the care of their family, mostly their parents, and many authors suggested that the school counselling services for these children are inseparable from their family and community. A qualitative research study was conducted with 12 secondary school counsellors from Perak state in Malaysia. The counsellors were interviewed to explore their experiences of working in the existing counselling services system. The findings showed that there was a lack of collaboration among various educational stakeholders and the resources from the community were not utilized effectively. As a result of this study, a comprehensive integrative model for school counselling is proposed and discussed. Some possible challenges faced by counsellors and suggestions on ways to further improve counselling services within the Malaysian context are discussed.